Development and psychometric validation of an age-friendly health system assessment tool in the Iranian context - Badriyeh Karami; Maryam Tajvar; Abbas Ostadtaghizadeh; Mehdi Yaseri (Health Research Policy and Systems, 2024)
Abstract Evaluating health system interventions for elderly care necessitates a context-specific, credible and dependable instrument. This research was dedicated to creating and validating a tool to assess the health system’s age-friendliness. The study unfolded in two pivotal stages: the generation of items utilizing a hybrid model and the psychometric appraisal of the tool, encompassing both validity and reliability assessments. From an initial pool of 522 items derived from a systematic scoping review and qualitative analysis, a concise assessment tool emerged, featuring 52 items across 6 domains: governance, information, resources, service delivery, community engagement and outcomes. The 52-item tool offers a straightforward, substantiated and robust means to gauge age-friendliness, pinpoint health system deficiencies and facilitate strategic planning on the basis of its insights.